Evaporative cooling performance of alkali-activated tungsten mine waste mud mortars - Salazar, María Victoria Bastardo (2011)
The increase on energy demand associated to the substantial use of air conditioning systems, requires careful consideration of passive cooling strategies with evaporative cooling to be a useful technique for this purpose. An important factor influencing the performance of evaporative cooling systems is the material that acts as a medium in the evaporation process. In these study there were experimentally determined the evaporative cooling properties of some geopolymer materials that are made by using of mining waste mud. The main objective of this study was to develop a geopolymer-based material having adequate properties for evaporative cooling to be used in a complex passive cooling unit under research development. The experimental work was based on the use of a test tunnel previously designated to other evaporative cooling research, where other types of materials where analyzed. Results show that geopolymer materials show good behavior for this type of testing, and the best of them were the composition with the coarse sand as an aggregate.